Effect of butanol and salt concentration on solid-state nanopores resistance - Vega, Milena (2016)
The objective of this study was to demonstrate the possibility of using 1-butanol to reliably detect the open-pore current of pyramidal solid-state nanopores produced in silicon wafers. The nanopores were produced through controlled pore formation by neutralizing an etchant (KOH) with a strong acid (HCl). Since nanopores produced by this method are deeper than those made in nanometer-thick membranes, they behave as nanochannels. As a consequence, the open-pore current detection is more challenging. Thus, we report that low amounts of butanol considerably aid in the detection of the open-pore current of nanopores.